Blood Fibrinolytic System in Rana tigrina - Srivastava, V M; Dube, B; Dube, R K; Agarwal, G P; Ahmad, N (Thrombosis and Haemostasis, 1981)
Fibrinolytic activity is well demonstrable in the blood of Rana tigrina. There occurs prompt lysis of diluted plasma; and the plasma euglobulin fraction shows lysis on both unheated and heated fibrin (human or bovine) plates, implying the presence of plasmin-like enzyme in this fraction. The fibrinolytic activity is remarkably inhibited by the erythrocyte-lysate and is moderately enhanced by leucocytes-thrombocytes. EACA suppresses the lysis of dilute cell-free plasma clots at concentration of l0-4M or more, possibly indicating the presence of plasminogen activator in the plasma. Activation of fibrinolysis by human urokinase and not by streptokinase, shows the probable presence of plasminogen and absence of proactivator.
Keywords: Fibrinolysis in Rana tigrina; Blood cells in fibrinolysis; Erythrocytic inhibition of fibrinolysis; Fibrinolysis enhancement by leucocytes-thrombocytes; Plasmin-like enzyme in Rana tigrina